A study on the use of banks financial technologies in the states of the European Union - Aistė Padvilikytė; Kristina Garškaitė-Milvydienė (Mokslas: Lietuvos Ateitis, 2024)
The article analysis financial technologies and their relevance and usefulness in the existing financial market. The work presents and analyzes the services (models) provided by financial technologies, they can be divided into payments, asset management, crowdfunding, lending, and the capital and insurance market. The main and most popular services provided by banks, which are related to financial technologies, are presented. A SWOT analysis of financial technologies is also presented, which shows the advantages and disadvantages of FinTech. The services provided by financial technologies are very diverse, they are provided by both ordinary companies and banks. This article focuses on financial technology that is provided by banks – internet usage: internet banking, number of ATMs, credit transfers in a state, percentage of population in a state, which shows how many people have a debit or credit card and whether those residents have received or made a digital transfer. In the third part, using multi-criteria evaluation methods: CRITIC and EDAS and performing cluster analysis, European Unions are compared and ranked.